Edukasi Perilaku Hidup Bersih Sehat Pada Siswa SDN Malei Tojo Kabupaten Tojo Una-Una - C, Christine; F, Fellysca (Yayasan Daarul Huda Kruengmane, 2024)
Improving public health can begin by fostering clean and healthy living habits from an early age through the implementation of Clean and Healthy Living Behavior (PHBS) in elementary schools. This study aims to enhance students' understanding of PHBS, encourage healthy behavior changes, and measure the effectiveness of education through pre-test and post-test methods. The activity was conducted at SDN Malei Tojo, Tojo Una-Una Regency, using educational methods such as leaflets, lectures, and demonstrations.Pre-test results indicated that students lacked awareness of the importance of PHBS, such as proper handwashing and disposing of waste appropriately. After the education sessions, post-test results showed a 30% improvement in students' understanding, particularly in handwashing with soap and reducing the consumption of unhealthy snacks. While the education positively influenced students' behavior, continuous guidance is necessary to ensure these habits become integral to their daily lives. Recommendations for schools include regular monitoring, involving parents, and initiating innovative programs such as cleanliness competitions to support PHBS implementation in schools.